Nature of perennating structures of Peronospora destructor - B.R. THAKUR; P.D. TYAGI, S.K. SUGHA, R.K. DEVELASH, B.M. SINGH (Indian Phytopathology, 2002)
P. destructor, the incitant of downy mildew of onion, survives as mycelium and oospores in seeds and other parts of onion plants. Mycelium in volunteer plants on garbage heaps and infected onion bulbs constituted the potential source of inoculum tothe subsequent onion crop in Himachal Pradesh, India.